Best of spirituals gospels fifty nine great songs: easy arrangements for one and two voices - Harris, Bill (Editorial Schott, 2003)
Contains 59 great songs in PVG. Titles include: Amazing grace, Amen, Deep River, Down by the Riverside, Dry Bones, Every Time I Feel the Spirit, Gimme That Old Time Religion, I'm Gonna Sing, Kum Ba Yah, Nobody Knows the Trouble I've Seen, Oh Happy Day, Rock My Soul, Steal Away, Swing Low Sweet Chariot, This Train Is Bound For Glory, Wade In The Water, Over In The Gloryland, Rise And Shine, Go Tell It On The Mountain, The Angel Rolled The Stone Away, Didn't My Lord Deliver Daniel and many more.